The association between oral health status and physical function in elderly patients with acute heart failure - Yusuke Uemura; Rei Shibata; Shinji Ishikawa; Kenji Takemoto; Toyoaki Murohara; Masato Watarai (Wiley, 2024)
Abstract Objectives Oral health problems are common and are associated with various geriatric conditions in older adults. The importance of oral health has not been fully highlighted in the assessment and management of patients with heart failure. Here, we investigated the association between oral health status and the decline in physical function during hospitalization in elderly patients with acute heart failure. Materials and Methods We evaluated oral health using the revised oral assessment guide in 77 patients aged 65 years or older who were admitted to hospital for acute heart failure. Oral health problems were defined as a revised oral assessment guide score ≥9. Results Oral health problems were identified in 66.2% of the patients. Patients with oral health problems had high prevalence of decreased physical function, undernutrition, and cognitive impairment. A reduction in the Barthel Index, as an indicator of activities of daily living during hospitalization, was significant in the enrolled patients. The Barthel Index decreased more in patients with oral health problems than those with normal oral health. Furthermore, the revised oral assessment guide score on admission was found to be the only independent predictor of changes in the Barthel Index during hospitalization in the multivariate analyses. Conclusions Oral assessment using the revised oral assessment guide during hospitalization could provide useful information for the management of elderly heart failure patients.